Analisis Investasi Mudharabah Berjangka Sebagai Intrumen Dana Darurat Bagi Generasi Z dalam Perspektif Keuangan Syariah - satria ilham; Panji Adam Agus Putra; Siska Lis Setiani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The low level of financial literacy among Generation Z has significantly affected their ability to manage personal finances, particularly in preparing emergency funds. From an Islamic finance perspective, term-based mudharabah investment offers an alternative that emphasizes not only profitability but also the principles of justice, honesty, and transparency between the capital provider (shahibul maal) and the fund manager (mudharib). This article aims to analyze the potential of term-based mudharabah as an emergency fund instrument for Generation Z by employing a qualitative conceptual literature approach. The analysis indicates that mudharabah investment possesses characteristics that align well with the objectives of emergency fund formation, as its profit-sharing mechanism provides a more equitable return compared to interest-based conventional instruments. Furthermore, the underlying Islamic values promote ethical and sustainable financial management. However, the limited understanding of Islamic financial instruments and the consumerist tendencies among Generation Z remain major obstacles to the broader adoption of this scheme. Therefore, stronger financial literacy education and innovative mudharabah products with flexible liquidity features are required to meet the needs of younger investors. Consequently, term-based mudharabah can serve as an effective and Sharia-compliant solution to enhance Generation Z’s financial resilience through ethical and well-managed emergency fund planning.